Design and construction of an instrumented meteorological tethersonde (2007)
The observations of the planetary boundary layer are key to the realization of the numerical weather forecast. Systems for shaping the atmosphere generally have a high price, which often makes them inaccessible. Therefore, the need for low-cost measuring instruments that allow reliable data to be obtained has led to the design and construction of an instrumented captive weather balloon, comparable to the various systems existing in the international market such as radiosondeo, wind profilers, SODARS and captive balloons, among others. By lowering the cost, the possibility of carrying out a greater number of quality measurements, useful in studies of atmospheric processes that determine the weather, but above all to improve the initial condition of the weather forecasting models, opens up. This article describes the design of a low-cost captive weather balloon with which boundary layer measurements can be maintained continuously, useful in atmospheric process studies and in the numerical weather forecast. The viability of the instrument was demonstrated in measurement campaigns carried out on board an oceanographic vessel.